Nationwide survey of Pharmacist’s involvement in antimicrobial stewardship program in Nigerian Tertiary Hospitals - Abubakar, Usman; Tangiisuran, Balamurugan (Elsevier Ltd, 2019)
Objectives To evaluate the participation and the barriers to hospital pharmacists’ participation in antimicrobial stewardship program (ASP) in Nigerian tertiary hospitals.